Availability and structure of primary medical care services and population health and health care indicators in England - Adams Geoffrey; Jack Ruth H; Gulliford Martin C; Ukoumunne Obioha C (BMC, 2004)
Abstract Background It has been proposed that greater availability of primary medical care practitioners (GPs) contributes to better population health. We evaluated whether measures of the supply and structure of primary medical services are associated with health and health care indicators after adjusting for confounding. Methods Data for the supply and structure of primary medical services and the characteristics of registered patients were analysed for 99 health authorities in England in 1999. Health and health care indicators as dependent variables included standardised mortality ratios (SMR), standardised hospital admission rates, and conceptions under the age of 18 years. Linear regression analyses were adjusted for Townsend score, proportion of ethnic minorities and proportion of social class IV/ V. Results Higher proportions of registered rural patients and patients ≥ 75 years were associated with lower Townsend deprivation scores, with larger partnership sizes and with better health outcomes. A unit increase in partnership size was associated with a 4.2 (95% confidence interval 1.7 to 6.7) unit decrease in SMR for all-cause mortality at 15-64 years (P = 0.001). A 10% increase in single-handed practices was associated with a 1.5 (0.2 to 2.9) unit increase in SMR (P = 0.027). After additional adjustment for percent of rural and elderly patients, partnership size and proportion of single-handed practices, GP supply was not associated with SMR (-2.8, -6.9 to 1.3, P = 0.183). Conclusions After adjusting for confounding with health needs of populations, mortality is weakly associated with the degree of organisation of practices as represented by the partnership size but not with the supply of GPs.